Inter-rater reliability of self-reported response on foreskin status in questionnaire among Japanese adult men. Issue 7 (24th May 2012) - Yamagishi, Takuya; Imai, Hirohisa; Nakao, Hiroyuki; Yahata, Yuichiro; Iizuka, Norio; Onoye, Yasuhiko; Koichi, Udagawa; Misaki, Hiroshi; Takaaki, Ohyama
Abstract : Objectives: To determine whether foreskin status is a measurable marker for evaluating the effect of the foreskin on sexually transmitted infections. Methods: Inter-rater comparison of the responses on foreskin status and circumcision in a self-report questionnaire with the findings of a physical examination by an experienced well-trained urologist was performed for patients who visited a healthcare facility in Kanagawa, Japan. Foreskin status was defined using a five-point graphical scale based on the degree to which the foreskin covers the foreskin and the glans penis in a non-erectile condition: type 1, a fully exposed glans penis; types 2–4, the glans penis partly covered by the foreskin and type 5, phimosis. Linear weighted κ and per cent agreement were used to evaluate the reliability of responses. Results: Among 188 participants who were evaluated about their foreskin status, linear weighted κ and per cent agreement were 0.74% and 68.4%, respectively. Linear weighted κ improved from 0.74 to 0.80 when the number of categories was changed to three. All the self-reported responses on circumcision were in agreement with the findings of the physical examination. Seventeen participants (9.0%) had been circumcised, and among them, three (17.6%) had approximately one-half of their glans penis covered by the foreskin. In 90 among the 171 uncircumcised participants (52.6%), the foreskin did not cover the glans penis. Conclusions: The self-reported response on foreskin status in this questionnaire has sufficient reliability to replace physical examination, and this questionnaire can facilitate further studies about the effect of foreskin on sexually transmitted infections.